Impact analysis and vibration reduction design of spiral bevel gears. (September 2019) - Mu, Yanming; Fang, Zongde; Li, Wenli
To minimize the running vibration of spiral bevel gear, an optimization design method for vibration control is presented with the model of meshing impact. Firstly, based on the impact model of spiral bevel gears considering tooth deformation, the initial meshing position, meshing stiffness, and the meshing impact is studied. Secondly, the effects of load torque and rotation speed on meshing impact are analyzed. Thirdly, a mathematical model for pinion generator is built with following parameters: tool parameters, initial machine settings, and polynomial coefficients of auxiliary flank modification motion. The polynomial coefficients of the auxiliary flank modification motion are determined by optimizing the minimum impact velocity. Finally, a numerical simulation is performed. The results shows that load torque and pinion rotational speed impose significant influences on the impact. The impact velocity increases with the increase of load torque and pinion rotation speed. With load torque increasing, impact force tends to increase first and then decrease because of meshing stiffness changes, finally impact force increases dramatically due to additional load. The advantages of spiral bevel gear under the optimization of impact velocity in meshing impact are obviously. The accuracy and scientificity of the method presented in the paper for calculating the initial meshing point and meshing stiffness of complicated tooth surfaces is verified. The optimized gear obtained by the optimization method presented in the paper is also proved that owns the lowest meshing impact in the design load range. The proposed optimization method can reduce meshing impact and improve the dynamic meshing performance of spiral bevel gear. This method also can be used for optimum design of other types of gears.